Opportunities for Hydrogen Recovery from Seawater Electro-Chlorination in Desalination Plants for Sustainable Energy Transition: A Perspective Review - Jimenez-Arevalo, V; Jimenez-Arevalo, V (Elsevier B.V., 2026)
This work highlights an underexplored opportunity in the hydrogen economy: the systematic recovery of hydrogen inherently produced during seawater electrochlorination in operational desalination plants. Unlike conventional electrolysis, which requires high-purity water and dedicated infrastructure, this approach valorises hydrogen generated as a by-product of an established disinfection process, converting a commonly vented stream into a strategic clean-energy resource. Electrochlorination, traditionally focused on chlorine generation, is here redefined as a dual-purpose process for both water treatment and the production of green hydrogen. Reported operational data show hydrogen yields of 63–70 mL/L at pressures of 34–68 bar, with energy demands as low as 2.3–2.8 kWh/m3 H₂ in advanced hybrid systems compared with 5.6–6.7 kWh/m3 in direct seawater electrolysis. The study integrates technical, economic, and environmental dimensions, analysing challenges such as the competitive chlorine evolution reaction, electrode corrosion, and fouling, while discussing enabling advances in catalyst design, membrane engineering, and alternative anodic reactions. Techno-economic evaluations indicate that coupling desalination–electrochlorination systems with photovoltaic energy can reduce CAPEX and OPEX significantly, achieving levelized hydrogen costs of $1.2–1.5 per kg H₂ alongside valuable co-products such as chlorine and sodium hydroxide. Particularly suited to high-irradiance coastal regions, such as northern Chile (>2800 kWh/m2/year solar potential), this scalable and cost-effective paradigm aligns with Chile s National Green Hydrogen Strategy. It offers transformative opportunities for small- and medium-sized enterprises in aquaculture, agro-industry, and wastewater treatment. By reframing an existing water treatment technology as a hydrogen platform, this study introduces a disruptive, high-impact pathway that contributes to Sustainable Development Goals (SDGs 6, 7, and 13), advances circular economy principles, and accelerates the global energy transition. © 2025 Elsevier B.V.